2021
DOI: 10.3390/jmse9060586
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Monoculture and Polyculture of Striped Catfish and Nile Tilapia in Different Proportions and Their Effects on Growth Performance, Productivity, and Financial Revenue

Abstract: Cultivation of species of high growth rates is a key achievement of sustainable aquaculture development, with the aim of increasing animal protein per capita, maintaining food security and preserving freshwater usage. The present study was conducted to evaluate the feasibility of monoculture and polyculture of striped catfish, Pangasianodon hypophthalmus, and Nile tilapia, Oreochromis niloticus, in different proportions and their effect on growth performance, survival, productivity, feed utilization, body comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…The present findings strongly relate to those of Tibihika et al (2020), Hura et al (2018), Iram et al (2013) and Solomon et al (2007) who reported that increase in dietary protein level in fish diet is favorable for proper fish growth. However, contrasting findings have been reported by Aslam et al (2017), Mansour et al (2021) andIslam et al (2017) who reported that lipid and other ingredients included in diets may greatly affect the fish growth. Overall production of ponds of treatment T 2 was more than that of the T 1 and control ponds.…”
Section: Discussionmentioning
confidence: 76%
“…The present findings strongly relate to those of Tibihika et al (2020), Hura et al (2018), Iram et al (2013) and Solomon et al (2007) who reported that increase in dietary protein level in fish diet is favorable for proper fish growth. However, contrasting findings have been reported by Aslam et al (2017), Mansour et al (2021) andIslam et al (2017) who reported that lipid and other ingredients included in diets may greatly affect the fish growth. Overall production of ponds of treatment T 2 was more than that of the T 1 and control ponds.…”
Section: Discussionmentioning
confidence: 76%
“…El costo de las dietas experimentales se calculó en dólar de los Estados Unidos (USD). El análisis de la relación costobeneficio se calculó multiplicando los costos de la dieta por el FCA y así obtener el ahorro por concepto de alimentación de las dietas experimentales con relación al grupo control (T0), en la producción de un kg de tilapia, según Palupi et al (21) y Mansour et al (22).…”
Section: Materiales Y Métodosunclassified
“…It is a valuable source of essential nutrients, especially high-quality protein and fats (macronutrients), vitamins, and minerals (micronutrients) that make a vital contribution to the world's food and nutrition security ( 3 ). As a food product, fish is of greater importance in developing countries where it accounts for 75% of the daily animal protein, referred to as “rich and poor food” as an important companion ( 4 , 5 ). Compared with other animal protein sources, fish is readily available even in poorer communities at a relatively cheaper price.…”
Section: Introductionmentioning
confidence: 99%